"The Living, The Dead, The Undecided": An Annotated Bibliography of Law Review Articles Dealing with the Law of Absentees and Returnees. (8th September 2016) - Jarvis, Robert M.; Chaney, Megan F.
Abstract: Over the years, the legal problems posed by absentees and returnees have attracted the attention of scores of law review authors. Their work is difficult to access, however, because it is scattered across time and place. This is particularly problematic for a field that has no current organizing text. Accordingly, this bibliography collects and annotates the more notable pieces, dividing them into three principal categories: General Works, State-Specific Works, and Subject-Specific Works.